10-year outcome trajectories of people with mental illness and their families who receive services from multidisciplinary case management and outreach teams: protocol of a multisite longitudinal study - Mai Iwanaga; Koji Yoshida; Sayaka Sato; Sosei Yamaguchi; Chiyo Fujii; Mariko Watanabe; Kaori Usui; Takayuki Kawaguchi; Ayako Hada; Masaaki Nishio; Hidemaro Yanata; Kenichirou Taniguchi; et al. (BMJ Open)
Introduction Individuals with mental illness and their families often undergo their recovery process in their communities. This study explored the long-term outcome trajectories of individuals and families who received case management services provided by multidisciplinary outreach teams in a community setting. The primary objective of this study was to determine whether trajectories of subjective quality of life (QoL) related to personal recovery were linked to those clinical and societal outcomes and changes in outreach service frequency.Methods and analysis The protocol of this 10-year multisite cohort study was collaboratively developed with individuals with lived experience of psychiatric disorders who had received services from participating outreach teams, and with family members in Japanese family associations. The participants in the study include patients and their key family members who receive services from 23 participating multidisciplinary outreach teams. The participant recruitment period is set from 1 October 2023 to 30 September 2025. If necessary, the recruitment period may be extended and the number of participating teams may be increased. The study will annually evaluate the following outcomes after participants’ initial utilisation of services from each team: QoL related to personal recovery, personal agency, feelings of loneliness, well-being and symptom and functional assessments. The family outcomes encompass QoL, well-being, care burden and family relationships. Several meetings will be held to monitor progress and manage issues during the study. Multivariate analyses with repeated measures will be performed to investigate factors influencing changes in the patients’ QoL scores as the dependent variable.Ethics and dissemination The study protocol was approved by the ethical committee of the National Center of Neurology and Psychiatry (no. A2023-065). The study findings will be reported in peer-reviewed publications and presented at relevant scientific conferences.Trial registration number UMIN-CTR, No. UMIN000052275.